2020
DOI: 10.1101/2020.09.23.310797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociated development of speech and limb sensorimotor learning in stuttering: speech auditory-motor learning is impaired in both children and adults who stutter

Abstract: Stuttering is a neurodevelopmental disorder of speech fluency. Various experimental paradigms have demonstrated that affected individuals show limitations in sensorimotor control and learning. However, controversy exists regarding two core aspects of this perspective. First, it has been claimed that sensorimotor learning limitations are detectable only in adults who stutter (after years of coping with the disorder) but not during childhood close to the onset of stuttering. Second, it remains unclear whether st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 105 publications
(137 reference statements)
1
10
0
Order By: Relevance
“…However, our between-subject analysis showed that responses to gradual perturbations were like sudden perturbations (except in the change phase) for formant-shift and formant-clamp perturbations. The results for gradually vs. suddenly introduced formant-shift perturbations are consistent with the results of previous studies (Kearney et al, 2020; Kim et al, 2020; MacDonald et al, 2010). These results may be related to the fact that the within-subject analysis is more sensitive to detect potential effects (for a review, see Charness et al, 2012) of the sudden and gradual introduction of perturbations.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, our between-subject analysis showed that responses to gradual perturbations were like sudden perturbations (except in the change phase) for formant-shift and formant-clamp perturbations. The results for gradually vs. suddenly introduced formant-shift perturbations are consistent with the results of previous studies (Kearney et al, 2020; Kim et al, 2020; MacDonald et al, 2010). These results may be related to the fact that the within-subject analysis is more sensitive to detect potential effects (for a review, see Charness et al, 2012) of the sudden and gradual introduction of perturbations.…”
Section: Discussionsupporting
confidence: 92%
“…Our results may also have clinical implications. For example, we have previously shown that adaptive responses to auditory perturbations are significantly small (or nonexistent) for adults who stutter (Daliri et al, 2017; Daliri & Max, 2018; Kim et al, 2020; Max & Daliri, 2019). Previously, we interpreted the small adaptive responses of people who stutter as lower sensitivity to errors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations